Learning jQuery : better interaction design and web development with simple Javascript techniques. - Chaffer, Jonathan, ....-; Swedberg, Karl, ....- (Birmingham : Packt, 2007)
JQuery is a powerful JavaScript library that can enhance your websites regardless of your background. In this book, creators of the popular jQuery learning resource, learningquery.com, share their knowledge, experience, and enthusiasm about jQuery to help you get the most from the library and to make your web applications shine. For designers, jQuery leverages existing CSS and HTML skills, allowing you to dynamically find and change any aspect of a page. This book provides a gentle introduction to jQuery concepts, allowing you to add interactions and animations to your pages-even if previous attempts at writing JavaScript have left you baffled. For programmers, jQuery offers an open -source, standards-compliant, unobtrusive approach to writing complex JavaScript applications. This book will guide you past the pitfalls associated with AJAX, events, effects, and advanced JavaScript language features, as well as provide you with a reference to the jQuery library to return to again and again. This book begins with a tutorial to jQuery, followed by an examination of common, real-world client-side problems, and solutions for each of them. A detailed reference rounds off the book, making it an invaluable resource for answers to all your jQuery questions. Who this book is written for This book is for web designers who want to create interactive elements for their designs, and for developers who want to create the best user interface for their web applications. The reader will need the basics of HTML and CSS, and should be comfortable with the syntax of JavaScript. No knowledge of jQuery is assumed, nor is experience with any other JavaScript libraries required.
Keywords: Programmeren